Analysis Characteristics DGEM Mixture Using Mixed Filler Husk Ash Waste Rice And Lime off - meliana, siti rissa; nikmah, alfi alfiatun; budirahardjo, slamet budirahardjo; Suwandi, Putri Anggi Permata (Science and Technology Research Centre, Universitas PGRI Semarang, 2022)
Husk ash paddy generated from remainder burning bricks still _ _ have score low benefit , from _ Thing this conducted experiment mixing Among waste ash husk rice and lime off as replacement filler filler on mix asphalt emulsion CRS-1 type . Use mixture cold with asphalt emulsion no cause pollution as well as friendly environment . Destination in study this is analyze characteristics Dense Graded Emulsion Mix (DGEM) using mixed filler waste ash husk rice and lime off.Composition use of mixed fillers waste ash husk rice and lime off by 60% ash husk rice and 40% lime solid , 70% ash husk rice and 30% lime extinguished , and 80% ash husk rice and 20% lime extinguished , with a curing period of 3, 7 and 11 days with the curing method is carried out inside temperature room and immersion . Mixture waste ash husk rice and lime off best customized with percentage comparison that is testing stability highest with limit minimum specification 300 kg of mixed filler composition (60% ABS + 40% KP) with a curing period of 11 days .Â Keywords : Asphalt _ Emulsion , Waste , DGEM , Stability .